HAM DAN PERANG MELAWAN TERORISME (STUDI TENTANG KEBIJAKAN AMERIKA SERIKAT DI PENJARA GUANTANAMO) - Riska Anggraini Putri; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Terrorism is an act that can threaten the security and sovereignty of all countries, including the United States. The September 11 incident which brought down the World Trade Center (WTC) building triggered the United States to launch a global war against terrorism with various policies in it. The war against terrorism is enough to give rise to new impacts and problems, especially in the issue of human rights and has an impact on the Muslim community. The theory used in this study is a realism approach using the theory of international regimes, where the state is considered the main actor and the most important actor in analyzing politics. And national security is the main issue compared to other issues related to security which dominate towards politics. The research method uses qualitative research with descriptive analysis, with data collection techniques namely secondary data. Through library research techniques (library research). The results of this study show that the United States has committed gross human rights violations at Guantanamo Prison with various forms of torture due to the implementation of the United States version of the clash of cultures and the justification for the pre-emptive strike and pre-emptive self-defense policies that it implements as a form of war against terrorism. The United States is a superpower or a powerful country so no one can change its policies. Keywords: Terrorism, policy, Human Rights, Guantanamo